Identifikasi Faktor Yang Mempengaruhi Sukses Wirausaha - Edy Purwo Saputro; Nur Achmad; Sih Handayani (Benefit: Jurnal Manajemen dan Bisnis, 2016)
Entrepreneurship is one of essential factors that contributing for economic development. The role of women entrepreneur is pivotal in this regard. This study examined factors that influencing the success of women’s entrepreneur. This study used 231 respondents that located in Solo. The data gathered are analyzed by structural equation model. The result indicated that micro, macro, performance and capability positively influenced to the success of entrepreneur.